Torakochirurgia Primary malignant melanoma of the cervical oesophagus – a rare tumour in a very rare location - Krishnadas, Rakesh; Froeschle, Peter; Day, David; Berrisford, Richard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
We report a case of primary malignant melanoma arising most unusually in the cervical oesophagus. A 78-year-old woman presented with an eight-month history of progressive shortness of breath and stridor, and an enlarging neck lump associated with dysphagia. Apart from a multinodular goitre and a parathyroid adenoma, investigations revealed a polypoid mass in the cervical oesophagus close to the cricopharynx. Biopsy of the lesion showed a primary malignant melanoma. No pigmented lesions of the skin or eyes were found. Endoscopic debulking of the tumour was performed and the patient received palliative percutaneous radiotherapy. Although 238 cases of primary oesophageal malignant melanoma have been reported in literature, none of these malignancies was localised in the cervical oesophagus.